Дослідна установка та результати досліджень по вивченню процесів замороження води на вертикальній трубі - Пилипенко, Олексій Юрійович; Засядько, Ярослав Іванович (My University, 2012)
Запропоновано диференціальне рівняння визначення швидкості замороження води на зовнішній поверхні труби. Представлено схему експериментальної установки, план та результати дослідів по визначенню швидкості замороження води та танення льоду на вертикальній циліндричній поверхні при її повздовжньому обтіканні теплоносієм. Наведено результати експериментів. A differential equation aimed at the determination of ice build-up on the external tubular surface has been developed. An experimental rig for the studies into the ice time rate build-up and ice thawing is presented with the placements of all measuring devices and transducers. The details of the refrigeration contour operation have been analyzed together with its interaction with the water contour, in with the process of icing on the cooled vertical tubes takes place. A developed methodology and a program of experiments along with the ranges of phase flow rates and temperature are given in great details. The samples of the temperature –time histories at the characteristic points of the experimental rig illustrate the data sets obtained. An initial set of the ice growth time rate data along with the line depicting ice melting are also give within the article.
Keywords: диференціальне рівняння; cold accumulators; акумуляція; експериментальна установка; лід; вода; холод; ice; water; measurements; determination; кафедра теплоенергетики та холодильної техніки